Promoting Student Understanding of Occupation-Centered Practice and Updated Inter-Rater Reliability of the Occupation-Centered Intervention Assessment - Kelly Little; Yongyue Qi; Vanessa D. Jewell (Journal of Occupational Therapy Education, 2023)
The Occupation-Centered Intervention Assessment (OCIA) was developed as a reflective tool for students to improve their comprehension of occupation-centered practice. Finding new and innovative ways to incorporate occupation-centered assignments can serve as a strategy to develop student integration of occupation-centered practice and allow educators to appraise student comprehension. The purpose of this study was to evaluate student understanding of occupation-centered practice by utilizing various statistical analyses, including updated inter-rater reliability, of the OCIA using student assignments. Utilizing a methodological approach, 121 first-year students analyzed 10 physical rehabilitation videos utilizing the OCIA to rate the interventions for their level of occupation-centeredness. Overall, the students demonstrated good agreement (α =.864), indicating the OCIA has good inter-rater reliability with first year students. Individual and aggregate student OCIA scores and standard deviations provided valuable information to the course instructors for threshold concepts to reinforce throughout the course and program. The use of the OCIA facilitates student comprehension and application of occupation-centered reasoning and can be woven into didactic curricula as a learning tool.